Analysis of the Effectiveness of the Performance of Flyover using VISSIM: A Case Study of Satdobato Intersection - Gautam, Bismita; Bajimaya, Arjeena; Karki, Anuska; Yadav, Gaurav Krishna; Balami, Bibek; Shrestha, Pradeep Kumar (International Journal on Engineering Technology and Infrastructure Development, 2025)
Satdobato, a major junction in Lalitpur, is a congested area with high-density traffic. Field surveys revealed that traffic volumes exceed the intersection's capacity, leading to congestion. To reduce traffic delay, a new scenario with a flyover on the existing road was analyzed. PTV VISSIM, a microscopic simulation tool, was used to simulate intersection capacity and traffic performance. The flyover allowed main traffic to move uninterrupted, resulting in a 51% decrease in overall delay, a 55% decrease in average queue length, and notable improvement in average travel time. Also, the level of service improved from E to D, indicating enhanced traffic efficiency.